Men and masculinities in south India - Osella, Caroline; Osella, Filippo (Anthem South Asian studies., 2006)
"Men and Masculinities in South India aims to increase understanding of gender within South Asia and especially South Asian masculinities, a topic whose analysis and ethnographising in the region has had a very sketchy beginning and is ripe for more thorough examination. This is, in short, an almost empty field dominated so far by short articles and collections and the time is right for the first full-length ethnographic study of masculinities. This ground-breaking monograph covers a range of areas including work, cross-sex relationships, sexuality, men's friendships, religious practices and leisure."--Jacket